Induction melting of gamma-TiAl in CaO crucibles - Gomes, Fernando (2008)
In this work a Ti–48Al alloy was induction melted in a CaO crucible using different superheating temperatures. In the first stage, samples were allowed to cool to room temperature inside the crucibles, in order to simulate a low cooling rate, and in the second stage samples were centrifugally poured into a steel mould, in order to study the effect of the melting operation on the alloy contamination with oxygen. The effect of superheating temperature on the metal-crucible interaction, alloy chemical composition, microstructure and microhardness is evaluated. The CaO crucible was found to be slightly dissolved by the molten alloy and the extent of that dissolution depends on the superheating temperature. A relationship was found between oxygen concentration and microhardness profiles of the a2 þ g microconstituent, from the surface to the inside of samples, which depends on the superheating temperature and cooling rate